Análisis del sistema de puesta a tierra y apantallamiento eléctrico, mediante modelamiento en software para garantizar el funcionamiento y desempeño de las instalaciones, considerando una futura expansión en la central de generación “GASGREEN S.A.”, ubicada en el relleno sanitario del Distrito Metropolitano de Quito. - Changoluisa Chacha, Cristian Javier (2021)
This research work deals with the analysis of the shielding and grounding systems in the GasgreBiogas Plant because failures have occurred there, causing damage to the protection equipment in turn ihas been considered a future expansion. Thus, soil resistivity andgrounding resistance measurements were madtobtain values of up to 40.4 Ω-m and 986 Ω, respectively. Therefore, the systems were modeled in ETAP in initial and current conditions with the present value of soil resistivity 23.57 Ω-m. Besides, it determined the resistance of 0.588 Ω, a touch voltage of 854.4 V. It exceeded the tolerable values. Also, according to the modeling of the rolling spheres for the current shielding system made up of a dipole type lightning rod, it was determined the second stage of generators are outside the protection zone andupon expansion. This set of protections would not provide the necessary guarantees for the proper functioning of the plant. Improvements to the system were proposed that were verified by software. So, It got grounding values of 0.414 Ω and a touching voltage of 589 V. They are within thepermissible limits; in addition, to designing the third stage of the same. While for the modeled shielding system, it is suggested to use two piezoelectric lightning rods with a delta of 10 meters and a diameter to cover aleast 80 meters for the entire plant.